Response of Kansas Feral Rye Populations to Aggressor Herbicide and Management in CoAXium Wheat Production System - V. Kumar; R. Liu; T. Lambert (Kansas Agricultural Experiment Station Research Reports, 2020)
Feral rye (Secale cerealeL.), also commonly known as cereal or volunteer rye, is a troublesome winter annual grass weed species in wheat producing regions of the United States, including Kansas. Lack of effective herbicide options complicates the selective control of feral rye in winter wheat. The main objectives of this research were (1) to determine the response of 10 feral rye populations collected from central Kansas wheat fields to Aggressor herbicide in dose-response assays, and (2) to evaluate the effectiveness of Aggressor herbicide for feral rye control in CoAXium winter wheat in Kansas. Dose-response assays indicated that all tested feral rye populations from Kansas wheat fields were highly sensitive to Aggressor herbicide with GR90values (doses of Aggressor herbicide needed for 90% reductions in shoot biomass at 3 weeks after treatment) ranging from 4.2 to 9.3 fl oz/a. A field study conducted near Great Bend, KS, indicated that Aggressor herbicide applied at ≥ 10 fl oz/a in fall or spring timings provided an excellent end-season control (≥ 94 %) of feral rye in CoAXium winter wheat. Overall, these results suggest that effective feral rye control could be achieved with Aggressor herbicide in a CoAXium wheat production system in Kansas.
Keywords: Aggressor herbicide; CoAXium wheat; feral rye